KECERDASAN KEWIRAUSAHAAN (ENTREPRENEURIAL INTELLEGENCE) PETANI MUDA LULUSAN UNIVERSITAS PADJAJARAN - Gema Wibawa Mukti; Rani Andriani Budi Kusumo; Pandi Pardian (Universitas Galuh Ciamis, 2020)
Agriculture is a very prestigious business sector, because it plays an important role in providing food for humanity. But apparently this does not automatically attract the attention of the community, especially the younger generation to pursue the field of agricultural business, especially graduates of the Faculty of Agriculture. Young people who choose a career in agriculture are required to have good entrepreneurial intelligence so that they can see an obstacle as a positive challenge. The purpose of this study was to determine entrepreneurial intelligence from graduates of the Faculty of Agriculture who chose a career as a business actor in agriculture. The research method in this study is a qualitative design. In-depth observation (Sugiyono, 2012) to see entrepreneurial intelligence possessed by graduates of the Faculty of Agriculture engaged in agribusiness. The results showed that graduates of the Faculty of Agriculture who are engaged in agriculture have entrepreneurial intelligence such as (1) having the courage to take risks, (2) being able to recognize their strengths or potentials, where they have a clear vision in life, (3) having emotional intelligence good, (4) Always oriented to the process and results, (5) Adaptive to change, which is always willing to learn, change and develop following changes in markets and the environment, (6) Never stop innovating in the course of its business, (7) Able to always collaborate with other parties and work together positively with each other so that all parties can develop and succeed together - (8) Always build a business network (friendship) with partners and stakeholders related to their business, (9) Getting used to always provide benefits to the environment, sharing and advancing together so that they always have a positive spirit for success.